Analisis Pengembangan Wilayah Dan Sektor PotensialTerhadap Pembangunan Di Kabupaten BoyolaliTahun 2011-2015 - Yanti, Ulfa dewi; , Drs. Yuni Prihadi Utomo, M.M (2017)
This study entitled "Analysis of Regional Development and AgainstPotential Sector Development in oyolaliear2011-2015". The purpose of thisstudy was to analyze the economic growth in Boyolali based on its potential andanalyze the sector base in Boyolali as information and consideration evelopment planning and strategies for regional development.The data used inthis research is secondary data in the form of regional gross domestic product(GDP) Boyolali and Central Java province on the basis of constant prices in2011-2015 were obtained from BPS Boyolali and Central Java Province. The results showed the agriculture, forestry and fishing, mining andquarrying, wholesale and retail trade; repair of cars and motorcycles,transportation and warehousing sector, service sector companies, the servicesector of education, the health service sector and social activities, and other services sector is a sector basis. The sectors that have competitive value is themanufacturing sector, the service sector of education, transportation andwarehousing sector, information and communication sector, provision felectricity and gas, financial services and insurance, service sector companies,the construction sector, real estate sector, the service sector health and socialactivities, the sector provision of accommodation and eating and drinking. Then sector belonging to the sectors of advanced and rapidly growing sectors aremining and quarrying, transportation and warehousing, service sector companiesand other service sectors. Sectors included in the advanced but depressed sectorsnamely agriculture, forestry and fishing, wholesale and retail trade sector; repairof cars and motorcycles, the service sector of education and health services sector and social activities.